Column Removal of Some Dyestuffs by Activated Carbons Derived from Apricot Stone Shells - Laila B. Khalil; Badie S. Girgis (Adsorption Science & Technology)
Activated carbons (ACs) were prepared from apricot stone shells impregnated with H 3 PO 4 , followed by carbonization at 400–500°C. Fixed-bed removal of two dyestuffs, i.e. Direct Red 99 (DR) and Reactive Orange 11 (RO) was followed at constant bed height and flow rate. Several column characteristics were evaluated from the breakthrough curves obtained including: the volume and loading at breakpoint, the height of the mass transfer zone, the bed service time, the time and loading at exhaustion, and the fractional bed loadings at various stages. The bed performance with RO was better than for DR, which was ascribed to a screening effect towards the larger DR molecules and to enhanced adsorption arising from the polyhalogenated nature of the RO molecule. The removal of colour was favoured as the porosity of the AC developed, being particularly related to its mesoporosity and total pore volume.